Para‐Selective CH Amidation of Simple Arenes with Nitriles. Issue 16 (17th November 2015) - Xiang, Shi‐Kai; Li, Jin‐Mei; Huang, He; Feng, Chun; Ni, Hai‐Liang; Chen, Xiao‐Zhen; Wang, Bi‐Qin; Zhao, Ke‐Qing; Hu, Ping; Redshaw, Carl
Abstract: A para ‐selective CH amidation of simple arenes with nitriles has been developed. By increasing the amount of arenes, a further meta ‐selective CH arylation of the produced amides occurred. Both steric and electronic effects are utilized to control the selectivity, resulting in only para ‐selective amidation products. The readily available nitriles as amidation reagents instead of amides makes the synthesis of N ‐arylamides more accessible. Abstract :